Digitalization of Institutional Communication in Islamic Education: Opportunities and Challenges in the Era of Society 5.0 - Hafiz, Abdul; Burhan; Sari Dewi, Ratna; Ahmad Nizar, Rasya; Romdaniah, Leli; Mauliza, Syifa (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
The digitalization of institutional communication is an important phenomenon in various sectors, including Islamic education. The era of Society 5.0, which emphasizes the integration of technology into social and economic life, presents both challenges and new opportunities in communication within Islamic educational institutions. This article discusses the opportunities and challenges of digitalizing communication in Islamic education and its implications for the development of educational quality. Through a qualitative approach and literature review, this article explores various digital innovations that can be implemented in Islamic educational institutions and their impact on communication processes among institutions, teachers, and students. Additionally, this article identifies barriers that need to be addressed to ensure that digital communication is optimally utilized within the context of Islamic education.